Accelerating anticancer drug development — opportunities and trade-offs. Issue 12 (December 2018) - Nass, Sharyl; Rothenberg, Mace; Pentz, Rebecca; Hricak, Hedvig; Abernethy, Amy; Anderson, Kenneth; Gee, Amanda; Harvey, R.; Piantadosi, Steven; Bertagnolli, Monica; Schrag, Deborah; Schilsky, Richard
Abstract The traditional approach to drug development in oncology, with discrete phases of clinical testing, is becoming untenable owing to expansion of the precision medicine paradigm, whereby patients are stratified into multiple subgroups according to the underlying cancer biology. Seamless approaches to drug development in oncology hold great promise of accelerating the accessibility of novel therapeutic agents to the public but are also accompanied by important trade-offs, including the limited availability of information on the clinical benefit and safety of novel agents at the time of market entry. In this Perspectives article, we describe several opportunities, in the form of novel trial designs or modelling strategies, to improve the efficiency of drug development in oncology, as well as new mechanisms to obtain information about anticancer therapies throughout their life cycle, such as innovative functional imaging techniques or the use of real-world clinical data. With the expansion of the precision medicine paradigm, seamless trial approaches to drug development hold great promise for accelerating the accessibility of novel therapeutic agents but are also accompanied by important trade-offs. The authors describe several opportunities to improve the efficiency of drug development in oncology, as well as new mechanisms to obtain information about anticancer therapies throughout their life cycle.